The Analysis of Code-Switching in My Nerd Girl: A Gender-Focused Sociolinguistic Study: English - Ni Putu Wida Pertami; Putu Nur Ayomi (Universitas Islam Negeri Palopo, 2026)
This study investigates how code-switching serves as a gendered linguistic strategy in the Indonesian web series My Nerd Girl, focusing on how male and female characters alternate between Bahasa Indonesia and English to express identity and perform social roles. Using a descriptive qualitative method and guided by Poplack’s (1980) typology, the research examined 223 instances of code-switching throughout the series. The findings show that inter-sentential switching is the most frequently used type among both genders; however, female characters switch codes more often and for different sociolinguistic reasons. While female characters commonly use code-switching to build solidarity, express identity, and navigate power dynamics, male characters tend to employ it for functions such as maintaining privacy, excluding others, and adding emphasis. These gendered patterns indicate that code-switching in the series is not used arbitrarily but is embedded with intentional social meaning shaped by narrative context. By situating the analysis within a fictional yet culturally resonant media text, the study highlights how language use in scripted dialogue can reflect and shape real-world gendered communication practices. The research contributes to the fields of sociolinguistics, gender studies, and media linguistics by offering a culturally grounded perspective on how multilingual language use intersects with gender in Indonesian popular media.